Evaluation of reliability in geodetic monitoring networks treated with Kalman filter - سخيه تمام (Latakia University Journal -Engineering Sciences Series, 2024)
You must be entitled geodetic monitoring networks accuracy conditions and permanence, and strength, and allergies, and the cost. Mathematically, the ideal design of a geodetic network requires minimizing or achieving a maximum of the cost function that indicates the quality of the network. Classically, a network can be optimized using the empirical method, error method, analytical methods, or by applying optimization techniques such as the Kalman filter algorithm. Therefore, the Kalman filter was used in designing and processing Geodetic monitoring networks Currently used to monitor strategic installations in country, which also enabled from Determine the system status, and check. This is in real time according to for the deformation model the appropriate. Which prompts geodesists to develop statistical tests for this filter, to verify the efficiency of treatment. In this search, evaluated the level of reliability and robustness in geodetic monitoring networks treated with the linear Kalman filter, and used to monitor the movement situation in the Tishreen Dam in Latakia. This article also discussed the alternative derivation of the distribution of surplus values, which represents the basic element in the Kalman filter reliability theory, and the research presented a set of conclusions and recommendations.